Close-coupling calculations for electron–atom collisions: benchmark studies and uncertainty estimates. (30th April 2015) - Bartschat, Klaus; Zatsarinny, Oleg
Abstract: Results from close-coupling calculations for electron collisions with a variety of atomic targets are presented. The agreement of the predictions with experiment as well as results from other sophisticated calculations provides an indication about the likely accuracy of the theoretical approach and its ability to provide sufficiently reliable and complete results for use in modeling calculations.